RISE: Energy justice in rural electrification: a case study of Rumah Panjang Tungan Batang Rajang, Kapit Sarawak / Assoc. Prof. Ir Dr Nofri Yenita Dahlan - Dahlan, Nofri Yenita (Office of the Deputy Vice-Chancellor (Research & Innovation), 2022)
A research team from Solar Research Institute (SRI), Universiti Teknologi MARA (UiTM) led by Assoc. Prof. Ir Dr Nofri Yenita Dahlan has partnered with researchers from the University of Leeds and University of Sussex, United Kingdom to conduct a research project titled "Facilitating a Just, Fair, and Affordable Energy Transition in the Asia- Pacific". A total grant of GBP 108,397.00 ~ RM 650,000.00 has been awarded by the British Academy under the Just Transition to Decarbonisation in the Asia-Pacific Programme 2021. The study aims to explore novel models for a just and equitable transition to renewable energy systems in the Asia-Pacific.